Pemikiran Ekonomi Abu Ubaid - Cici Ananta Siagian; Rahmad Ibrahim; Rayhan Tambak Bintang; Wafia Ningrum; Yara Az-zahra (Mutiara : Jurnal Penelitian dan Karya Ilmiah, 2024)
To date, there has been relatively little discussion or representation of Islamic economic theory in national economies. Early in Islamic history, a Muslim scholar named Abu 'Ubaid wrote extensively about economics and history. Abu Ubaid highlighted the philosophical underpinnings of later economic theories and ideas. Abu Ubaid concentrated on the idea of economic justice in law. The role of money as a store of value, medium of exchange, and exchange rate standard are all undoubtedly practiced in Islamic economics. Of course, some application of this way of thinking can be used as a basis for assessment and guidance in improving an economic system that is fair and beneficial to society. In certain respects, Indonesia's economic policy as a sovereign nation is in harmony with Abu Ubaid's economic theories and concepts. However, regarding suitability, the question is whether the current standing of the nation has fulfilled its purpose or is still in progress.